2021
DOI: 10.3390/jof7100875
|View full text |Cite
|
Sign up to set email alerts
|

Role of Protein Glycosylation in Interactions of Medically Relevant Fungi with the Host

Abstract: Protein glycosylation is a highly conserved post-translational modification among organisms. It plays fundamental roles in many biological processes, ranging from protein trafficking and cell adhesion to host–pathogen interactions. According to the amino acid side chain atoms to which glycans are linked, protein glycosylation can be divided into two major categories: N-glycosylation and O-glycosylation. However, there are other types of modifications such as the addition of GPI to the C-terminal end of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 152 publications
(290 reference statements)
1
21
0
Order By: Relevance
“…Still, most of the Efg1 core direct targets lack known or easily rationalized roles in biofilm or hypha formation. This limitation in our understanding may reflect functional redundancy ( 2 , 3 , 16 22 ) or perhaps the limited range of biofilm-related phenotypes that have been assayed in mutant analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Still, most of the Efg1 core direct targets lack known or easily rationalized roles in biofilm or hypha formation. This limitation in our understanding may reflect functional redundancy ( 2 , 3 , 16 22 ) or perhaps the limited range of biofilm-related phenotypes that have been assayed in mutant analyses.…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 30 , 36–38 This innermost layer is generally composed of chitin and β-glucans in Candida spp; 29 , 31–34 , 39–44 while the outermost layer contains proteins modified with both N -linked and O -linked mannans. 30 , 38 , 45–49 The C. lusitaniae mannan structure is significantly different from other Candida species and closer to that described in C. albicans , showing β-1,2-mannose residues as part of the N -linked mannan side chains. 50 In C. lusitaniae , the structural polysaccharides β-1,3-glucan and chitin, as in other Candida species, are located underneath the cell wall proteins, most of which are covalently linked to β-1,6-glucan by glycosylphosphatidylinositol anchors.…”
Section: Basic Biological Attributes Of Candida Lusitaniaementioning
confidence: 57%
“…30,33,84 The fungal cell wall is a highly dynamic structure that provides protection, controls communication with the extracellular environment, maintains cell integrity, and functions as a molecular scaffold to display virulence factors. 33,38,44,52 This structure has pathogen-associated molecular patterns (PAMPs), which are recognized by the immune system through PRRs, most of them located on the cell surface of immune cells. [85][86][87] The main PAMPs found in the different Candida species, such as C. guilliermondii, are chitin, β-1,3-and β-1,6-glucans, and N-linked and O-linked mannans.…”
mentioning
confidence: 99%
“…Some glycoproteins present on the fungal cell wall have been demonstrated to be required for pathogenicity and are absent from mammalian cells [ 16 , 17 , 18 , 19 ]; therefore, the genes required for their biosynthesis represent potential molecular targets to develop new medically relevant antifungal drugs. Even though other wall components are not by themselves virulence factors, glycoproteins are considered virulence determinants because the disruption of their biosynthesis affects cell fitness and, thus, the host-fungus interaction; this is the case of N -linked and O -linked glycans attached to cell wall proteins [ 9 , 13 , 20 , 21 , 22 , 23 ]. For example, rhamnose-based glycans are a minor cell wall component and therefore were not previously thought to contribute to an infecting process, but it was found that their synthesis is required for the pathogenicity of the vascular wilt fungus Verticillium dahliae [ 24 ].…”
Section: Introductionmentioning
confidence: 99%